928 Development and validation of a survey on fathers' attitudes towards child injury prevention. (1st September 2016) - Olsen, Lise; Brussoni, Mariana; Ishikawa, Takuro; Masse, Louise; Chan, Grace
Abstract : Background: The purpose of this study was to develop and validate a survey instrument to measure fathers' attitudes regarding injury prevention for their children. Parents play an important role in reducing child injury risk; however, our understanding of the unique role that fathers play in keeping children safe is limited. Our previous research indicated that fathers believed risk played an important role in their children's development and that they aimed to balance these risks with protecting children from injury. Methods: We developed a survey to measure two main dimensions of fathers' parenting attitudes: child protection from injury (16 items) and child risk engagement (24 items). The survey content was created using a 4-step process utilising expert feedback, cognitive interviews with fathers and pilot-testing. The survey was administered to fathers of children ages 6–12 years visiting the Emergency Department of a children's hospital in British Columbia, Canada. We used confirmatory factor analysis to validate the factor structure of the questionnaire. Results: There were 302 fathers who completed the questionnaire, with 45% children attending hospital for an injury and 55% for another medical concern. Following analysis, the child protection from injury factor was found to consist of eight items (Cronbach's alpha of 0.75) and the child risk engagement factor consisted of six items (Cronbach's alpha of 0.77). Correlation between the factors was low suggesting the dimensions are independent. Conclusions: These survey data provide support for the idea that for fathers, child protection from injury and child risk engagement reflect distinct attitudinal dimensions. These results add to our understanding of fathers' conceptions related to child safety and offer direction for development of injury prevention messages and interventions that are tailored to fathers' perspectives and experiences.